Identities involving iterated integral transforms - Cyril Nasim (International Journal of Mathematics and Mathematical Sciences)
A number of identities involving iterated integral transforms are established, making use of the fact that a function which is a linear combination of the Macdonald's function Kν(z), where z is a complex variable, is a Fourier kernel.